Effect of microbial consortia on maize yield in Chiapas, Mexico - Rosabal , Lissy; Guevara Hernández, Francisco; Ruiz , Víctor; La O, Manuel; Raj, Deb; Reyes, Mariela (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The use of microbial consortia  as  biofertilizers  allows  improving  crop productivity and the quality of agricultural soils, by incorporating microorganisms that facilitate the availability of nutrients for plants and change the soil physicochemical conditions. In order to evaluate the effect of microbial consortia on maize yield, inoculums from different environments were used in the maize crop of Villa Corzo and Villaflores municipalities, Chiapas. Six treatments with different consortia were defined: three from agricultural plots and three from mountains “La Frailescana”, “Cerro Nambiyugua” and Biosphere Reserve “La Sepultura”-, and one control, under a randomized block experimental design with four replications. The application of the microbial consortia was made directly to the soil at 20, 40 and 60 days after sowing of the crop. The effect of the consortia on maize yield was determined using a design with nested effects in which the effects of the origin of the microbial consortia were controlled, and the nested treatments in the environments. The association between the physicochemical components of the consortia and the culture yield was evaluated using Pearson’s correlation (p ≤ 0.05). Only the mountain consortiums from “La Sepultura” were the ones that showed maize yield increase. However, both the mountain and plot consortiums have the potential to be used as biofertilizers in maize cultivation, when combined with another source of organic fertilization, such as poultry manure.